Maîtriser l’espace public. Chrono-topographie anthropologique d’un affrontement, Charonne (8 février 1962) - Marie-Vic Ozouf-Marignier (L'Atelier du CRH)
This contribution aims at emphasizing Alain Dewerpes’s interest for the spatial and temporal dimensions of political facts. When he described the confrontation between the policemen and the demonstrators during the events of February 8th, 1962, near the subway station Charonne, the author produced a sensitive geography of the appropriation of the public place. Dewerpe paid attention to the “ordinary” knowledge policemen and demonstrators used in the confrontation, and to the specific gestures, noises, rhythm and location of an event, the massacre of Charonne. In this way, Dewerpe was innovative in a rarely explored field: the spatiality and the temporality of the collective mobilizations.